The Evaluation of English Coursebook for Young Learners When English Rings a Bell: A Survey Research - Sahril Nur; Zul Astri; Sanaria Maneba; Fhadli Noer; Kasmawati Kasmawati (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
This research aimed to assess When English Rings a Bell, an introductory English textbook. In addition, this research seeks to examine one textbook used in seventh-grade classrooms. This research aims to determine if the goals of the English textbook When English Rings a Bell align with the principles of teaching English to young students. When English Rings a Bell, the researcher, the evaluation checklist from (Bilash, 2009), and the textbook's material served as the research instruments. Overall, the textbook seems like it would be a good fit for young learners in terms of several aspects, such as General Appearance, Layout and Design, Activities, and Language skills.). In addition, the textbook fulfills the principles of teaching for young learner